Legal Protection of Child Custody Rights After Divorce According to Article 41 of Law No. 1 of 1974: A Study at the Cianjur Religious Court - Lina Pusvisasari; Iwan Gustiawan Fadwi; Muhammad Luthfi Pratama (Pasundan Social Science Development, 2026)
This study aims to analyze the legal protection of child custody after divorce under Article 41 of Law Number 1 of 1974 concerning Marriage. The focus of this study is on the practice taking place at the Cianjur Class 1A Religious Court. This study uses an empirical juridical method with a descriptive qualitative approach. Data were obtained through observation, document study, and interviews with judges and court clerks. The results show that the protection of children's rights has been considered in the verdict, but its implementation still faces obstacles such as weak post-decision supervision, minimal parental legal awareness, and emotional conflict between parties. Judges use the principle of the best interest of the child and sometimes consider the results of mediation and the psychosocial conditions of the child and parents. Therefore, strengthening regulations, legal education, and the establishment of effective oversight mechanisms are needed to optimize legal protection for children.